Cardiovascular Disease Risk Assessment: a Review of Risk Factor-based Algorithms and Assessments of Vascular Health - Carrubba, Christopher Joseph; Blaha, Michael J.; Nasir, Khurram; DeFilippis, Andrew Paul (Current cardiovascular risk reports, 2014)
Risk factors related to the development of subclinical atherosclerosis and subsequent cardiovascular disease (CVD) events are well established. Starting with the Framingham Risk Score (FRS), several algorithms have been developed using these risk factors to predict the development of CVD, and the recent ACC/AHA guidelines recommend the use of new pooled cohort equations to predict 10-year risk for a first hard atherosclerotic cardiovascular disease (ASCVD) event in subjects 40–79 years of age. However, the limitations of these risk factor-based algorithms have been well documented and include decreased calibration when applied to populations outside of the initial cohort, inability to account for lifetime risk in younger populations, and the heterogeneity that exists between the presence of risk factors and actual atherosclerotic disease burden. As such, recent strategies have attempted to incorporate measurements of both vascular health, including carotid interna media thickness (CIMT), microalbuminuria, flow-mediated dilation (FMD) and aortic stiffness, and subclinical atherosclerosis through coronary artery calcium (CAC) screening into traditional risk assessment. Here, we review these different strategies for risk assessment and examine how these strategies can be combined to improve discrimination and reliability.